2002
DOI: 10.1037/h0095001
|View full text |Cite
|
Sign up to set email alerts
|

Students with mental illnesses in a university setting: Faculty and student attitudes, beliefs, knowledge, and experiences.

Abstract: Over the last decade, the topic of post-secondary supported education for people with severe and persistent mental illnesses has gained increasing attention and sparked interest in what colleges and universities can do to assist individuals with mental illnesses to achieve their educational goals. The purpose of this article is to discuss the issue and describe one university's strategy for improving the educational environment of students with psychiatric disabilities. We present findings from a survey design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 23 publications
4
68
0
2
Order By: Relevance
“…Similar to reports in previous studies (Baggett, 1994;Becker et al, 2002;Bourke et al, 2000;Leyser et al, 2011), most faculty expressed positive attitudes towards inclusion of students with disabilities in HE. In addition, consistent with previous research (e.g., Baggett, 1994), gender comparisons in this investigation indicated that female faculty have more positive attitudes than male faculty.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar to reports in previous studies (Baggett, 1994;Becker et al, 2002;Bourke et al, 2000;Leyser et al, 2011), most faculty expressed positive attitudes towards inclusion of students with disabilities in HE. In addition, consistent with previous research (e.g., Baggett, 1994), gender comparisons in this investigation indicated that female faculty have more positive attitudes than male faculty.…”
Section: Discussionsupporting
confidence: 79%
“…Although findings are inconsistent across studies, some reveal that faculty and administrators have, in general, a positive attitude toward students with disabilities and are willing to provide appropriate accommodations (Baggett, 1994;Becker, Martin, Wajeeh, Ward, & Shern, 2002;Bourke, Strehorn, & Silver, 2000). On the other hand, students with disabilities attending colleges and universities can face challenges not only due to limited accessibility and delivery of support services but also due to the negative attitudes of peers and faculty members (Duquette, 2000;Tremblay et al, 2008).…”
Section: Faculty Attitudes Toward Students With Disabilitiesmentioning
confidence: 99%
“…Discrimination towards the mentally ill also comes from various segments of the general population. Previous research has shown that mentally ill people are 4 denied jobs, have difficulty finding housing (Feldman & Crandall, 2007) and are not wanted in educational settings (Becker, Martin, Wajeeh, Ward, & Shern, 2002). Phelan and Basow (2007) suggested that perceived dangerousness of mentally ill persons is the leading cause of discrimination, stigmatization and the desire for social distance.…”
Section: Dangerous Criminals or Misunderstood? Assessing Police Percementioning
confidence: 99%
“…El factor miedo es común a diversos estudios que evalúan las actitudes de los estudiantes afirmando algunos participantes tener miedo o sentirse incómodos ante aquellos estudiantes con enfermedad mental (Becker, Martin, Wajeeh, Ward y Shern, 2002), siendo esta una variable predictora del mal funcionamiento en la integración de aquellos diagnosticados con dicha etiqueta. En efecto, la percepción de peligrosidad, con el consiguiente miedo que esta conlleva, desemboca finalmente en conductas aprensivas o de evitación (Corrigan y Watson, 2002), así como, de forma consistente con la distancia social, componente de peso en el proceso de estigmatización .…”
Section: Discussionunclassified